ANALISIS PROSES POLITIK PEMBAHASAN DAN PENETAPAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) PROVINSI RIAU TAHUN ANGGARAN 2016 - Febrina, Rury; ', Isril (Nakhoda: Jurnal Ilmu Pemerintahan, 2016)
The process of preparing a work programs of regional goverments is an integral part ofthe state financial system which assosiated with establishment of APBN and APBD. This studieswill analyse the political processes during the discussion and establishment of Riau ProvinceAPBD in 2016. In general, there are 3 stages of discussion and establisment of Riau ProvinceAPBD in 2016 namely a discussion of KUA PPAS, framing a RANPERDA APBD, andestablisment of APBD. However a discrepancy in the implementation schedue to the prevailingregulation lead to a non optimal discussion RKA SKPD, RAPBD and RANPERDA APBD wherethe entire process is done on December 2016. The political process on discussion and establishmentof APBD on DPRD of Riau Province is observed on discussion of KUA PPAS that involvingTAPD and Budgetary Board.The general overview of DPRD fraction to the RAPBD will be answered by localgoverment and then DPRD plenary session wil be held to made a decision that supported by allDPRD members toward RAPBD to APBD, the plenary session will be concluded with the finalopinion of The Mayor.